(untitled) (Journal of Educational Sciences, 2023)
The development of science is one of the priority areas of state policy that ensures economic growth. The presence of publications in international journals is the basis for obtaining a degree, promotion and allocation of funds for research. In this regard, the term “fake science” is becoming increasingly popular in the academic world. This term refers to the process of imitation of science in order to obtain certain benefits. In this article, fake science is considered in the context of publications by students, doctoral students and other researchers in journals with unethical publishing practices. The aim of this work is to study the key characteristics of predatory journals and researchers who publish in them. The main directions are to determine the current state of the publication activity of Kazakh scientists, the motives of researchers who publish in predatory journals. The main hypothesis is that the influence of government policies has a negative impact on publishing practices, namely, it contributes to an increase in the proportion of articles in predatory journals. The scientific and practical significance of the work lies in the assessment of the ongoing scientific policy of the state. Based on the secondary analysis of the data, an analysis of the reasons why publications in low-quality journals are widespread is presented. Proposed measures to combat pseudoscience. Key words: publication practice, predatory journals, "fake science", publication activity, science policy